Response of Existing Pile Groups Due to Twin Tunneling: A Numerical Study - Ayasrah, Mo'men (Engineering, Technology & Applied Science Research, 2025)
Twin shield tunneling operations frequently cross pile group foundations at close intervals in densely populated areas. The relationship between recently built tunnels and pre-existing pile foundations has been extensively studied, but the impact of various twin-parallel shield tunneling construction sequences on pile groups has seldom ever been discussed. This work investigated the complex interrelationships of soil, pile group foundations, and twin tunnel excavation. The Tunnel Boring Machine (TBM) approach and three-dimensional Finite Element Analysis (FEA) were deployed using Midas GTS-NX to assess how pile groups respond to twin tunneling construction sequences. The results indicated that at a depth of 0.3D, the corner pile experiences a 60% greater effect than the middle pile as excavation progresses from 0 to +2D before stabilizing. Furthermore, the bending moment affects the entire pile length at 0.3D, but decreases by 48% and 60% as the tunnel depth increases to 0.7D and 1D, respectively.